Simulation Model to Assess Electrical Power Generation from Tidal Basin in Coastal Area Malaysia - K. Y., Kor; Shahrani, Anuar; Ahmmad Shukrie, Md Yudin; Hassan, Ibrahim; M., Mahendran (2014)
This article studies the numerical simulation of power generation in four different tidal stations in the East Coast region of Malaysia. The tidal stations are Tanjung Sedili, Tanjung Gelang, Tioman and Cendering. The simulation model is based on power generation using tidal barrage. Ebb, flood and double-mode generations were studied. The tidal basin area was estimated by approximation to generate sufficient electricity for local community consumption.